Bài giải mạch P16

Chia sẻ: Tran Thach | Ngày: | Loại File: PDF | Số trang:60

0
79
lượt xem
15
download

Bài giải mạch P16

Mô tả tài liệu
  Download Vui lòng tải xuống để xem tài liệu đầy đủ

Tham khảo tài liệu 'bài giải mạch p16', kỹ thuật - công nghệ, điện - điện tử phục vụ nhu cầu học tập, nghiên cứu và làm việc hiệu quả

Chủ đề:
Lưu

Nội dung Text: Bài giải mạch P16

  1. Chapter 16, Solution 1. Consider the s-domain form of the circuit which is shown below. 1 I(s) 1/s + 1/s − s 1s 1 1 I(s) = = 2 = 1 + s + 1 s s + s + 1 (s + 1 2) 2 + ( 3 2) 2 2  3  i( t ) = e - t 2 sin    2 t 3   i( t ) = 1.155 e -0.5t sin (0.866t ) A Chapter 16, Solution 2. s 8/s + + 4 − Vx 2 4 s −
  2. 4 Vx − s + Vx − 0 + Vx − 0 = 0 s 2 8 4+ s (16s + 32) Vx (4s + 8) − + (2s 2 + 4s)Vx + s 2 Vx = 0 s 16s + 32 Vx (3s 2 + 8s + 8) = s     s+2  0.25 + − 0.125 + − 0.125  Vx = −16 = −16 s(3s 2 + 8s + 8)  s 4 8 4 8  s+ + j s+ − j   3 3 3 3  v x = (−4 + 2e − (1.3333 + j0.9428) t + 2e − (1.3333 − j0.9428) t )u ( t ) V 2 2  6 − 4t / 3  2 2  vx = 4u ( t ) − e − 4 t / 3 cos  3 t −  e sin   3 t V    2   Chapter 16, Solution 3. s + 5/s 1/2 Vo 1/8 − Current division leads to:  1   1 5  5 5 Vo = 2 = = 8s1 1  10 + 16s 16(s + 0.625)  + +s 2 8  ( ) vo(t) = 0.3125 1 − e −0.625t u ( t ) V
  3. Chapter 16, Solution 4. The s-domain form of the circuit is shown below. 6 s + 1/(s + 1) + 10/s Vo(s) − − Using voltage division, 10 s  1  10  1  Vo (s) =  = 2   s + 6 + 10 s  s + 1  s + 6s + 10  s + 1  10 A Bs + C Vo (s) = = + 2 (s + 1)(s + 6s + 10) s + 1 s + 6s + 10 2 10 = A (s 2 + 6s + 10) + B (s 2 + s) + C (s + 1) Equating coefficients : s2 : 0= A+B  → B = -A s1 : 0 = 6A + B + C = 5A + C  → C = -5A 0 s : 10 = 10A + C = 5A  → A = 2, B = -2, C = -10 2 2s + 10 2 2 (s + 3) 4 Vo (s) = − 2 = − 2 − s + 1 s + 6s + 10 s + 1 (s + 3) + 1 2 (s + 3) 2 + 12 v o ( t ) = 2 e -t − 2 e -3t cos(t ) − 4 e -3t sin( t ) V Chapter 16, Solution 5. Io 2 2 1 s s s+2
  4.   1  1  = 1   2s  2s V=  2 =  (s + 2)(s + 0.5 + j1.3229)(s + 0.5 − j1.3229) s + 2 1 1 s  s + 2s + s + 2  + +  s 2 2 Vs s2 Io = = 2 (s + 2)(s + 0.5 + j1.3229)(s + 0.5 − j1.3229) (−0.5 − j1.3229) 2 (−0.5 + j1.3229) 2 1 (1.5 − j1.3229)(− j2.646) (1.5 + j1.3229)(+ j2.646) = + + s+2 s + 0.5 + j1.3229 s + 0.5 − j1.3229 ( ) i o ( t ) = e − 2 t + 0.3779e − 90° e − t / 2 e − j1.3229 t + 0.3779e 90° e − t / 2 e j1.3229 t u ( t ) A or ( ) = e − 2 t − 0.7559 sin 1.3229 t u ( t ) A Chapter 16, Solution 6. 2 Io 10/s 5 s s+2 Use current division. s+2 5 5s 5(s + 1) 5 Io = = = − 10 s + 2 s + 2s + 10 (s + 1) + 3 2 2 2 (s + 1) 2 + 3 2 s+2+ s 5 i o ( t ) = 5e − t cos 3t − e − t sin 3t 3
  5. Chapter 16, Solution 7. The s-domain version of the circuit is shown below. 1/s 1 Ix + 2s 2 s +1 – Z 1 (2s) 1 2s 2s 2 + 2s + 1 Z = 1 + // 2s = 1 + s = 1+ = s 1 1 + 2s 2 1 + 2s 2 + 2s s V 2 1 + 2s 2 2s 2 + 1 A Bs + C Ix = = x = = + Z s + 1 2s + 2s + 1 (s + 1)(s + s + 0.5) (s + 1) (s + s + 0.5) 2 2 2 2s 2 + 1 = A(s 2 + s + 0.5) + B(s 2 + s) + C(s + 1) s2 : 2=A+B s: 0 = A+B+C = 2+C  → C = −2 constant : 1 = 0.5A + C or 0.5A = 3  → A = 6, B = -4 6 4s + 2 6 4(s + 0.5) Ix = − = − s + 1 (s + 0.5) + 0.75 s + 1 (s + 0.5) 2 + 0.866 2 2 [ ] i x ( t ) = 6 − 4e − 0.5t cos 0.866 t u ( t ) A
  6. Chapter 16, Solution 8. 1 1 (1 + 2s) s 2 + 1.5s + 1 (a) Z = + 1 //(1 + 2s) = + = s s 2 + 2s s(s + 1) 1 1 1 1 3s 2 + 3s + 2 (b) = + + = Z 2 s 1 2s(s + 1) 1+ s 2s(s + 1) Z= 3s 2 + 3s + 2 Chapter 16, Solution 9. (a) The s-domain form of the circuit is shown in Fig. (a). 2 (s + 1 s) 2 (s 2 + 1) Z in = 2 || (s + 1 s) = = 2 + s + 1 s s 2 + 2s + 1 1 s 2 2 s 2/s 1/s 1 (a) (b) (b) The s-domain equivalent circuit is shown in Fig. (b). 2 (1 + 2 s) 2 (s + 2) 2 || (1 + 2 s) = = 3+ 2 s 3s + 2 5s + 6 1 + 2 || (1 + 2 s) = 3s + 2  5s + 6  s ⋅   5s + 6   3s + 2  s (5s + 6) Z in = s ||  = = 2  3s + 2   5s + 6  3s + 7s + 6 s +   3s + 2 
  7. Chapter 16, Solution 10. To find ZTh, consider the circuit below. 1/s Vx + 1V 2 Vo 2Vo - Applying KCL gives Vx 1 + 2Vo = 2 + 1/ s 2 But Vo = Vx . Hence 2 + 1/ s 4Vx Vx (2s + 1) 1+ =  → Vx = − 2 + 1/ s 2 + 1/ s 3s Vx (2s + 1) ZTh = =− 1 3s To find VTh, consider the circuit below. 1/s Vy + 2 2 Vo 2Vo s +1 - Applying KCL gives 2 V 4 + 2Vo = o  → Vo = − s +1 2 3(s + 1)
  8. 1 But − Vy + 2Vo • + Vo = 0 s 2 4  s + 2  − 4(s + 2) VTh = Vy = Vo (1 + ) = −  = s 3(s + 1)  s  3s(s + 1) Chapter 16, Solution 11. The s-domain form of the circuit is shown below. 4/s s 1/s + I1 I2 + 4/(s + 2) 2 − − Write the mesh equations. 1  4 =  2 +  I1 − 2 I 2 (1) s  s -4 = -2 I1 + (s + 2) I 2 (2) s+2 Put equations (1) and (2) into matrix form.  1 s   2 + 4 s - 2   I1   - 4 (s + 2)  =  - 2 s + 2  I 2       2 2 s 2 − 4s + 4 -6 ∆= (s + 2s + 4) , ∆1 = , ∆2 = s s (s + 2) s ∆1 1 2 ⋅ (s 2 − 4s + 4) A Bs + C I1 = = = + 2 ∆ (s + 2)(s + 2s + 4) s + 2 s + 2s + 4 2 1 2 ⋅ (s 2 − 4s + 4) = A (s 2 + 2s + 4) + B (s 2 + 2s) + C (s + 2) Equating coefficients : s2 : 1 2= A+B 1 s : - 2 = 2A + 2B + C
  9. s0 : 2 = 4 A + 2C Solving these equations leads to A = 2, B = -3 2, C = -3 2 - 3 2s − 3 I1 = + s + 2 (s + 1) 2 + ( 3 ) 2 2 -3 (s + 1) -3 3 I1 = + ⋅ + ⋅ s + 2 2 (s + 1) + ( 3 ) 2 2 2 3 (s + 1) + ( 3 ) 2 2 i1 ( t ) = [ 2 e -2t − 1.5 e -t cos(1.732t ) − 0.866 sin(1.732t )] u(t ) A ∆2 - 6 s -3 I2 = = ⋅ = ∆ s 2 (s + 2s + 4) (s + 1) + ( 3 ) 2 2 2 -3 i 2 (t) = e - t sin( 3t ) = - 1.732 e -t sin(1.732t ) u(t ) A 3 Chapter 16, Solution 12. We apply nodal analysis to the s-domain form of the circuit below. s Vo 10/(s + 1) + 1/(2s) 4 3/s − 10 − Vo 3 V s +1 o + = + 2sVo s s 4 10 10 + 15s + 15 (1 + 0.25s + s 2 ) Vo = + 15 = s +1 s +1 15s + 25 A Bs + C Vo = = + 2 (s + 1)(s + 0.25s + 1) s + 1 s + 0.25s + 1 2
  10. 40 A = (s + 1) Vo s = -1 = 7 15s + 25 = A (s 2 + 0.25s + 1) + B (s 2 + s) + C (s + 1) Equating coefficients : s2 : 0= A+B  → B = -A 1 s : 15 = 0.25A + B + C = -0.75A + C 0 s : 25 = A + C A = 40 7 , B = - 40 7 , C = 135 7 40 - 40 135 1 3 s+ 40 1 40 s+  155 2  7 7 7 2 2 Vo = + = − + ⋅  s +1  1 2 3 7 s +1 7  1 2 3  7 3   1 2 3 s +  + s +  + s +  +  2 4  2 4  2 4 40 - t 40 - t 2  3  (155)(2)  3  v o (t) = e − e cos   t +  e - t 2 sin   t  7 7  2  (7)( 3 )  2  v o ( t ) = 5.714 e -t − 5.714 e -t 2 cos(0.866t ) + 25.57 e -t 2 sin( 0.866t ) V Chapter 16, Solution 13. Consider the following circuit. 1/s 2s Vo Io 2 1/(s + 2) 1 Applying KCL at node o, 1 Vo Vo s +1 = + = V s + 2 2s + 1 2 + 1 s 2s + 1 o
  11. 2s + 1 Vo = (s + 1)(s + 2) Vo 1 A B Io = = = + 2s + 1 (s + 1)(s + 2) s + 1 s + 2 A = 1, B = -1 1 1 Io = − s +1 s + 2 i o ( t ) = ( e -t − e -2t ) u(t ) A Chapter 16, Solution 14. We first find the initial conditions from the circuit in Fig. (a). 1Ω 4Ω + 5V + io vc(0) − − (a) i o (0 − ) = 5 A , v c (0 − ) = 0 V We now incorporate these conditions in the s-domain circuit as shown in Fig.(b). 1 4 Vo Io 15/s + 2s 5/s 4/s − (b) At node o, Vo − 15 s Vo 5 Vo − 0 + + + =0 1 2s s 4 + 4 s
  12. 15 5  1 s  − = 1 + + V s s  2s 4 (s + 1)  o 10 4s 2 + 4s + 2s + 2 + s 2 5s 2 + 6s + 2 = Vo = Vo s 4s (s + 1) 4s (s + 1) 40 (s + 1) Vo = 5s 2 + 6s + 2 Vo 5 4 (s + 1) 5 Io = + = + 2s s s (s + 1.2s + 0.4) s 2 5 A Bs + C Io = + + 2 s s s + 1.2s + 0.4 4 (s + 1) = A (s 2 + 1.2s + 0.4) + B s s + C s Equating coefficients : s0 : 4 = 0.4A  → A = 10 s1 : 4 = 1.2A + C  → C = -1.2A + 4 = -8 2 s : 0= A+B  → B = -A = -10 5 10 10s + 8 Io = + − 2 s s s + 1.2s + 0.4 15 10 (s + 0.6) 10 (0.2) Io = − 2 − s (s + 0.6) + 0.2 2 (s + 0.6) 2 + 0.2 2 i o ( t ) = [ 15 − 10 e -0.6t ( cos(0.2 t ) − sin( 0.2 t )) ] u(t ) A Chapter 16, Solution 15. First we need to transform the circuit into the s-domain. s/4 10 Vo + Vx − + + 5 3Vx − 5/s − s+2
  13. 5 Vo − Vo − 3Vx Vo − 0 s+2 =0 + + s/4 5/s 10 5s 5s 40Vo − 120Vx + 2s 2 Vo + sVo − = 0 = (2s 2 + s + 40)Vo − 120Vx − s+2 s+2 5 5 But, Vx = Vo − → Vo = Vx + s+2 s+2 We can now solve for Vx.  5  5s (2s 2 + s + 40) Vx +  − 120Vx − =0  s + 2 s+2 (s 2 + 20) 2(s 2 + 0.5s − 40)Vx = −10 s+2 (s 2 + 20) Vx = − 5 (s + 2)(s 2 + 0.5s − 40) Chapter 16, Solution 16. We first need to find the initial conditions. For t < 0 , the circuit is shown in Fig. (a). To dc, the capacitor acts like an open circuit and the inductor acts like a short circuit. 2Ω Vo + − 1Ω 1F + 3V − + Vo/2 − 1H io (a)
  14. Hence, -3 i L (0) = i o = = -1 A , v o = -1 V 3  - 1 v c (0) = -(2)(-1) −   = 2.5 V 2 We now incorporate the initial conditions for t > 0 as shown in Fig. (b). 2 Vo + − 1 1/s s + + 2.5/s 5/(s + 2) I1 − I2 − − -1 V + Vo/2 − + Io (b) For mesh 1, - 5  1 1 2.5 Vo +  2 +  I1 − I 2 + + =0 s+2  s s s 2 But, Vo = I o = I 2  1  1 1 5 2.5  2 +  I1 +  −  I 2 = − (1)  s 2 s s+2 s For mesh 2,  1 1 V 2.5 1 + s +  I 2 − I1 + 1 − o − =0  s s 2 s 1 1 1 2.5 - I1 +  + s +  I 2 = −1 (2) s 2 s s
  15. Put (1) and (2) in matrix form.  1 1 1   5 2.5  2 + s −   I1   − 2 s   s+2 s    =   -1 1 1    2.5   s + s +  I 2   −1   2 s  s  3 4 5 ∆ = 2s + 2 + , ∆ 2 = -2 + + s s s (s + 2) ∆2 - 2s 2 + 13 A Bs + C Io = I2 = = = + 2 ∆ (s + 2)(2s + 2s + 3) s + 2 2s + 2s + 3 2 - 2s 2 + 13 = A (2s 2 + 2s + 3) + B (s 2 + 2s) + C (s + 2) Equating coefficients : s2 : - 2 = 2A + B 1 s : 0 = 2A + 2 B + C 0 s : 13 = 3A + 2C Solving these equations leads to A = 0.7143 , B = -3.429 , C = 5.429 0.7143 3.429 s − 5.429 0.7143 1.7145 s − 2.714 Io = − = − s+2 2s 2 + 2s + 3 s+2 s 2 + s + 1.5 0.7143 1.7145 (s + 0.5) (3.194)( 1.25 ) Io = − + s+2 (s + 0.5) 2 + 1.25 (s + 0.5) 2 + 1.25 [ ] i o ( t ) = 0.7143 e -2t − 1.7145 e -0.5t cos(1.25t ) + 3.194 e -0.5t sin(1.25t ) u(t ) A
  16. Chapter 16, Solution 17. We apply mesh analysis to the s-domain form of the circuit as shown below. 2/(s+1) + − I3 1/s s 1 I1 I2 1 4 For mesh 3, 2  1 1 +  s +  I 3 − I1 − s I 2 = 0 (1) s +1  s s For the supermesh,  1 1  1 +  I1 + (1 + s) I 2 −  + s  I 3 = 0 (2)  s s  But I1 = I 2 − 4 (3) Substituting (3) into (1) and (2) leads to  1  1  1  2 + s +  I 2 − s +  I 3 = 4 1 +  (4)  s  s  s  1  1 -4 2 - s +  I 2 + s +  I 3 = − (5)  s  s s s +1 Adding (4) and (5) gives 2 2 I2 = 4 − s +1 1 I2 = 2 − s +1
  17. i o ( t ) = i 2 ( t ) = ( 2 − e -t ) u(t ) A Chapter 16, Solution 18. 3 e −s 3 vs(t) = 3u(t) – 3u(t–1) or Vs = − = (1 − e − s ) s s s 1Ω + Vs + 1/s 2Ω − Vo − Vo − Vs V + sVo + o = 0 → (s + 1.5)Vo = Vs 1 2 3 2 2  Vo = (1 − e − s ) =  − −s (1 − e ) s(s + 1.5)  s s + 1.5  v o ( t ) = [(2 − 2e −1.5t )u ( t ) − (2 − 2e −1.5( t −1) )u ( t − 1)] V Chapter 16, Solution 19. We incorporate the initial conditions in the s-domain circuit as shown below. 2I 2 V1 Vo − + I + 4/(s + 2) 1/s 2 − 1/s s
  18. At the supernode, 4 (s + 2) − V1 V1 1 +2= + + sVo 2 s s 2  1 1 1 + 2 =  +  V1 + + s Vo (1) s+2 2 s s V1 + 1 But Vo = V1 + 2 I and I= s 2 (V1 + 1) Vo − 2 s s Vo − 2 Vo = V1 +  → V1 = = (2) s (s + 2) s s+2 Substituting (2) into (1) 2 1  2s + 1  s  2  + 2− =   Vo − + s Vo s+2 s  s  s + 2  s + 2  2 1 2 (2s + 1)  2s + 1   +2− + =  +s V s+2 s s (s + 2)  s + 2   o   2s 2 + 9s 2s + 9 s 2 + 4s + 1 = = Vo s (s + 2) s+2 s+2 2s + 9 A B Vo = = + s + 4s + 1 s + 0.2679 s + 3.732 2 A = 2.443 , B = -0.4434 2.443 0.4434 Vo = − s + 0.2679 s + 3.732 Therefore, v o ( t ) = ( 2.443 e -0.2679t − 0.4434 e -3.732t ) u(t ) V
  19. Chapter 16, Solution 20. We incorporate the initial conditions and transform the current source to a voltage source as shown. 2/s 1 1/s Vo + − + 1/(s + 1) 1 s 1/s − At the main non-reference node, KCL gives 1 (s + 1) − 2 s − Vo Vo Vo 1 = + + 1+1 s 1 s s s s +1 − 2 − s Vo = (s + 1)(s + 1 s) Vo + s +1 s s s +1 − − 2 = (2s + 2 + 1 s) Vo s +1 s - 2s 2 − 4s − 1 Vo = (s + 1)(2s 2 + 2s + 1) - s − 2s − 0.5 A Bs + C Vo = = + 2 (s + 1)(s + s + 0.5) s + 1 s + s + 0.5 2 A = (s + 1) Vo s = -1 =1 - s 2 − 2s − 0.5 = A (s 2 + s + 0.5) + B (s 2 + s) + C (s + 1) Equating coefficients : s2 : -1 = A + B  → B = -2 s1 : -2 = A+ B+C  → C = -1 s0 : - 0.5 = 0.5A + C = 0.5 − 1 = -0.5 1 2s + 1 1 2 (s + 0.5) Vo = − 2 = − s + 1 s + s + 0.5 s + 1 (s + 0.5) 2 + (0.5) 2 v o ( t ) = [ e -t − 2 e -t 2 cos(t 2)] u(t ) V
  20. Chapter 16, Solution 21. The s-domain version of the circuit is shown below. 1 s V1 Vo + 2/s 2 1/s 10/s - At node 1, 10 − V1 s V − Vo s s2 = 1 + Vo  → 10 = ( s + 1)V1 + ( − 1)Vo (1) 1 s 2 2 At node 2, V1 − Vo Vo s = + sVo  → V1 = Vo ( + s 2 + 1) (2) s 2 2 Substituting (2) into (1) gives s2 10 = ( s + 1)( s + s / 2 + 1)Vo + ( − 1)Vo = s ( s 2 + 2s + 1.5)Vo 2 2 10 A Bs + C Vo = = + 2 s ( s + 2s + 1.5) s s + 2s + 1.5 2 10 = A( s 2 + 2 s + 1.5) + Bs 2 + Cs s2 : 0 = A+ B s: 0 = 2A + C constant : 10 = 1.5 A → A = 20 / 3, B = -20/3, C = -40/3 20  1 s+2  20  1 s +1 0.7071  Vo =  s − s 2 + 2 s + 1.5  = 3  s − ( s + 1) 2 + 0.70712 − 1.414 ( s + 1) 2 + 0.70712  3     Taking the inverse Laplace tranform finally yields v o (t) = 20 3 [ ] 1 − e − t cos 0.7071t − 1.414e − t sin 0.7071t u ( t ) V
Đồng bộ tài khoản